Nest architectures of myrmecophilous stingless bees, Trigona cfr. cilipes and Paratrigona sp., from Peruvian Amazon - Marconi, Marilena; Modesti, Alessandro; Vecco Giove, Carlos Daniel; Mancini, Emiliano; Di Giulio, Andrea (Fragmenta entomologica, 2022)
Stingless bees (Hymenoptera: Meliponini) are corbiculate and eusocial bees, including over 500 species distributed in the tropical and sub-tropical regions of the world. They establish perennial colonies using a large variety of nesting sites, as well as colonies of ants, wasps and termites. Compared to termitophily, myrmecophily is an uncommon feature and little studied aspect among Meliponini. In Peru there are few records relating to these types of associations, and in general little is known about the architecture of the nests of bees and ants that live together. For the first time, the nest architecture of Trigona cfr. cilipes in association with Dolichoderus quadridenticulatus is described from the Peruvian Amazon. The record of another association, Paratrigona sp. - Camponotus sp. is also reported. As the nests are arranged, the types of building materials used and some behavioral defense observations of ants and bees are also provided.